Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Mai Thị Thanh xuân

Phân tích đa thức thành nhân tử :

x3 + x2 + 4

2x3 - 3x2 + 3x - 1

3x3 - 14x2 + 4x + 3

Phạm Hồ Thanh Quang
14 tháng 7 2017 lúc 8:43

   x3 + x2 + 4
= x3 + 2x2 - x2 - 2x + 2x + 4
= x2(x + 2) - x(x + 2) + 2(x + 2)
= (x + 2)(x2 - x + 2)

   2x3 - 3x2 + 3x - 1
= 2x3 - x2 - 2x2 + x + 2x - 1
= 2x2(x - 1/2) - 2x(x - 1/2) + 2(x - 1/2)
= (x - 1/2)(2x2 - 2x + 2)
= 2(x - 1/2)(x2 - x + 1)

   3x3 - 14x2 + 4x + 3
= 3x3 + x2 - 15x2 - 5x + 9x + 3
= 3x2(x + 1/3) - 15x(x + 1/3) + 9(x + 1/3)
= (x + 1/3)(3x2 - 15x + 9)
= 3(x + 1/3)(x2 - 5x + 3)


Các câu hỏi tương tự
linh nguyễn
Xem chi tiết
Nguyễn Đức Tài
Xem chi tiết
Dung Vu
Xem chi tiết
Dương
Xem chi tiết
Vy trần
Xem chi tiết
Vy trần
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Nguyễn Ngọc Anh
Xem chi tiết
Pham Trong Bach
Xem chi tiết